Identifikasi Bakteri Indigen Penghasil Enzim Protease Sebagai Agen Bioremediasi Limbah Laundry - Rahmi, Nisrina Afiqah (CV.ITTC INDONESIA, 2023)
The group of enzymes known as proteases are widely used in industry. Proteases are chemicals that hydrolyze peptide bonds in proteins into oligopeptides and amino acids. When compared to other sources, such as proteases from animals and plants, proteases from bacteria are the most common. Proteolytic microbes are microorganisms equipped to degrade proteins, producing extracellular protease compounds. This study aims to determine the potential of laundry waste bioremediation agents in producing proteolytic bacteria. The research method is by experimenting directly starting with taking samples of laundry waste, then isolating it to get bacterial colonies, and purifying it so that later it will be easier to get proteolytic bacteria.